2018
DOI: 10.21451/1984-3143-ar2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Influences of nutrition and metabolism on reproduction of the female ruminant

Abstract: Beef cows and ewes grazing native pastures are exposed to cycles of undernutrition that reflect the seasonal variations of biomass production. In grazing dairy cows, the physiological undernutrition during early lactation due to increased demands for lactation and low dry matter intake is exacerbated by the need to get sufficient intake from pasture and the extra grazing energy costs. Undernutrition has profound impacts on reproduction by affecting multiple reproductive processes at different levels of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Field studies have investigated various traits, including dietary managements, rearing environments, genetic selection [ 3 ], and disease status of both the systemic and genital tract, especially during the perinatal period, the most critical period for preparation and establishment of next pregnancy in dairy cows. In this regard, studies have aimed to elucidate the relationship between metabolic status (such as negative energy balance (NEB)) and the uterus (including parturition such as dystocia and retained placenta) during the perinatal period, and that between postpartum ovarian function and/or reproductive efficacy of cows [ 3 , 4 ]. We recently reported the efficacy of vaginal discharge score (VDS) in diagnosis of clinical endometritis and demonstrated that the VDS grading system improved dairy herd reproductive performance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have investigated various traits, including dietary managements, rearing environments, genetic selection [ 3 ], and disease status of both the systemic and genital tract, especially during the perinatal period, the most critical period for preparation and establishment of next pregnancy in dairy cows. In this regard, studies have aimed to elucidate the relationship between metabolic status (such as negative energy balance (NEB)) and the uterus (including parturition such as dystocia and retained placenta) during the perinatal period, and that between postpartum ovarian function and/or reproductive efficacy of cows [ 3 , 4 ]. We recently reported the efficacy of vaginal discharge score (VDS) in diagnosis of clinical endometritis and demonstrated that the VDS grading system improved dairy herd reproductive performance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this adaptation, feeding is key for the meat and milk production (Morand-Fehr et al, 2007), the herds health and reproduction (Lamy et al, 2012). Fecundation (Abecia et al, 2006), gestation, birth, and lactation are risk stages (in which they require more energy) for females (Kilgour et al, 2008;Kind et al, 2006;Meikle et al, 2018;Rosa and Bryant, 2003), for what feeding must be controlled to ensure the survival of the offspring. Especially in a context where autumn lambing could be envisaged and will be investigated, a special attention could have been given to winter food provisioning, aiming at reducing weight loss in prevision to spring mating (Tornero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that nutrition assumes an especially significant role during the late gestation time of does. The nutritional requirements of does during this period are influenced by the balance of blood metabolism and nutrients [ 19 ]. However, Sultana et al [ 8 ] found no significant differences in kids‘ BW in black Bengal goats after concentrate diet supplementation of dams.…”
Section: Discussionmentioning
confidence: 99%